Formation and characterization of organic silicon and fluoropolymers film on epoxy base for corrosion protection of carbon steel - Nguyen, Thuy Duong; A. E. Salamianski; A. A. Rogachev; V. M. Akulova; G. B. Melnikova; Tran, Dai Lam; Vu, Ke Oanh; Pham, Gia Vu; Nguyen, Anh Son; To, Thi Xuan Hang (Vietnam Journal of Science and Technology, 2024)
Coating systems using epoxy resin, organic silicon compounds (octadecyltrichlorosilane (OTS) and hydrolyzed heptadecafluoro tetrahydro decyltrimethoxysilane (HDFS)), and fluoropolymers (polytetrafluoroethylene (PTFE), and polyvinylidene fluoride (PVDF)), were applied to carbon steel. Epoxy (EP) coating and EP/OTS, EP/HDFS systems were produced via spin coating, while PTFE and PVDF layers were deposited using electron beam dispersion. Wettability, surface structure, and tribological properties were assessed through contact angle measurement, Fourier transform infrared reflection (FTIR), and tribotechnical test. Anticorrosion resistance was evaluated using electrochemical techniques, salt spray, and adhesion tests. Surface modifications with silicon compounds and fluoropolymers increased hydrophobicity, anticorrosion behavior and wear resistance. The water contact angles of EP, EP/OTS, EP/HDFS, EP/PVDF, and EP/PTFE were 84°, 108º, 116º, 96º, and 128º, respectively. Coating treatments reduced the friction coefficient. No corrosion was observed on treated surfaces after 336 hours in a salt spray chamber, while untreated EP showed rust after 96 hours. The hydrophobic systems based on epoxy resin, silicon compounds, and fluoropolymers are effective for protecting metal structures, with fluoropolymers providing higher protection to silicon compounds.